Personality traits in patients with skin diseases - Evgeniya V. Dvoriankova; Nikolay A. Shevchenko (LLC "MEDIAFORMAT", 2022)
Skin diseases have a significant effect on various aspects of patients' life and can cause psycho-emotional and psychosocial problems, as well as social maladaptation. Typical personality traits and personality types of the patients have been reported for a number of skin disorders. Psychological or even psychiatric disorders associated with the effects of chronic psycho-emotional stress prevail in patients with acne. These patients often suffer from depression and anxiety disorders. The type D personality characteristics are typical for patients with psoriasis: these patients experience strong negative emotions that are not, however, demonstrated due to fear of disapproval and rejection. This results in discomfort, selfdoubt, propensity for anxiety, and self-recrimination. Studying innate personality traits in patients with certain disorders is important for health care providers to understand the features of the patients' responses and their adherence to treatment, as well as to detect the concomitant psycho-emotional disorders and mental diseases. Better understanding of the patients' psychological features makes it possible to use targeted approaches to treatment of the disease-associated psychosocial problems, as well as to increase the disease. The paper reports a clinical case of psoriasis personality shown by the patient with acne.